2003
DOI: 10.1159/000075105
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Decompression for Trigeminal Neuralgia in Patients with Multiple Sclerosis

Abstract: Aims: To assess whether microvascular decompression (MVD) is a safe and efficacious treatment for patients with trigeminal neuralgia (TGN) and multiple sclerosis (MS). Methods: Case records were reviewed of all patients with TGN and MS who underwent posterior fossa exploration with a view to MVD between 1993 and 2001. In all patients, magnetic resonance tomoangiography (MRTA) demonstrated vascular compression. Results: Nine patients were included in the study. Seven patients underwent MVD alone; in 2 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 13 publications
0
31
0
4
Order By: Relevance
“…Even in this former case some authors suggested less efficacy and increased side effects for MS-related TN cases, e.g. Broggi et al [31] and Eldridge et al [32] for microvascular decompression, Kanpolat et al [5] for radiofrequency lesioning and Kondziolka et al [6] for glycerol rhizotomy. This is probably related to a different physiopathological context, disease related.…”
Section: Discussionmentioning
confidence: 99%
“…Even in this former case some authors suggested less efficacy and increased side effects for MS-related TN cases, e.g. Broggi et al [31] and Eldridge et al [32] for microvascular decompression, Kanpolat et al [5] for radiofrequency lesioning and Kondziolka et al [6] for glycerol rhizotomy. This is probably related to a different physiopathological context, disease related.…”
Section: Discussionmentioning
confidence: 99%
“…1). Thirty-eight met the inclusion criteria (Alstadhaug et al, 2008; Andrade et al, 2012; Athanasiou et al, 2005; Balasa and Bajko, 2010; Bentley et al, 2002; Broggi et al, 2004; Burkey and Abla-Yao, 2010; Carrieri et al, 2009; Cordella et al, 2009; Cruccu et al, 2009; da Silva et al, 2005; Davey and Al-Din, 2004; Deppe et al, 2013; de Santi et al, 2009; Donat, 2012; Eldridge et al, 2003; Fragoso and Brooks, 2007; Gass et al, 1997; Gee et al, 2005; Gentile et al, 2007; González-Quintanilla et al, 2012; Haas et al, 1993; Hellwig et al, 2006; Kister et al, 2010; Leandri et al, 1999; Liu et al, 2008; Marchettini et al, 2006; Meaney et al, 1995; Minagar and Sheremata, 2000; Nakashima et al, 2001; Pichiecchio et al, 2007; Ramirez-Lassepas et al, 1992; Svendsen et al, 2011; Tanei et al, 2010; Tortorella et al, 2006; Tosi et al, 1998; Vilisaar and Constantinescu, 2006; Yetimalar et al, 2008). Of these, 16 were case reports (Alstadhaug et al, 2008; Andrade et al, 2012; Bentley et al, 2002; Burkey and Abla-Yao, 2010; Carrieri et al, 2009; Davey and Al-Din, 2004; Donat, 2012; Gentile et al, 2007; González-Quintanilla et al, 2012; Haas et al, 1993; Leandri et al, 1999; Liu et al, 2008; Pichiecchio et al, 2007; Tanei et al, 2010; Tosi et al, 1998; Vilisaar and Constantinescu, 2006), nine were case series (Athanasiou et al, 2005; Cordella et al, 2009; de Santi et al, 2009; Fragoso and Brooks, 2007; Hellwig et al, 2006; Marchettini et al, 2006; Meaney et al, 1995; Minagar and Sheremata, 2000; Nakashima et al, 2001), and 13 were investigational studies (<...>…”
Section: Resultsmentioning
confidence: 99%
“…We found that field strength was specified in 15 studies (39% of all studies). Of these 15 studies, one tesla scanners were used in two studies (Balasa and Bajko, 2010; da Silva et al, 2005), 1.5 T scanners were used in nine studies (Eldridge et al, 2003; Gass et al, 1997; Gee et al, 2005; Meaney et al, 1995; Nakashima et al, 2001; Pichiecchio et al, 2007; Svendsen et al, 2011; Tortorella et al, 2006; Yetimalar et al, 2008), and 3 T scanners were used in two (of the most recent) studies (Andrade et al, 2012; Deppe et al, 2013). Scanners of varying strengths were employed in two studies: 0.6, 1.5 and 3 T (Kister et al, 2010), and 0.5 and 1.5 T (Broggi et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be interesting to see if from trigeminal reflexes a signal could be detected that would suggest a superiority of one treatment over the other. Case series even with somewhat variable results show no convincing superiority of any surgical method in this patient group [37][38][39][40]. Given that ganglion and root level neuroablative procedures are less invasive and therefore easier to tolerate by patients, many of whom have significant disability, they may be considered as first-line surgical interventions, with microvascular decompression left for nonresponders.…”
Section: Trigeminal Neuralgiamentioning
confidence: 87%